2021
DOI: 10.1039/d1ra03470g
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus speciation analysis of fatty-acid-based feedstocks and fast pyrolysis biocrudes via gel permeation chromatography inductively coupled plasma high-resolution mass spectrometry

Abstract: Renewable feedstocks, such as lignocelulosic fast pyrolysis oils and both vegetable oil and animal fats, are becoming a viable alternative to petroleum for producing high-quality renewable transportation fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…A more comprehensive understanding of the impact that the chemical composition of direct liquefaction biocrudes has on upgrading is becoming possible as more advanced methods are developed for characterizing biocrudes and the hydrotreated biocrude products. , Correlating the oxygen content of direct liquefaction intermediates with biocrude upgrading performance can be extended to evaluating the impact of individual components with specific oxygen functionality on the performance of hydrotreating catalysts. The various pyrolysis technologies being developed produce biocrude intermediates with a wide range of oxygen contents that depend on the catalyst, process conditions (temperature, pressure, hydrogen partial pressure), and feedstock. , …”
Section: Discussionmentioning
confidence: 99%
“…A more comprehensive understanding of the impact that the chemical composition of direct liquefaction biocrudes has on upgrading is becoming possible as more advanced methods are developed for characterizing biocrudes and the hydrotreated biocrude products. , Correlating the oxygen content of direct liquefaction intermediates with biocrude upgrading performance can be extended to evaluating the impact of individual components with specific oxygen functionality on the performance of hydrotreating catalysts. The various pyrolysis technologies being developed produce biocrude intermediates with a wide range of oxygen contents that depend on the catalyst, process conditions (temperature, pressure, hydrogen partial pressure), and feedstock. , …”
Section: Discussionmentioning
confidence: 99%
“…Analysis was achieved using ICP-MS with an assortment of internal standards introduced as a mixture on-line rather than being spiked into individual samples. The internal standards used were 45 Sc for those elements with a mass up to and including 59 Co, 72 Ge for the analytes 62 Ni to 95 Mo, 125 Te for 101 Ru to 137 Ba, 175 Lu for the analytes 189 Os to 197 Au and 209 Bi for analytes with a higher mass. Any polyatomic interferences were removed through the introduction of helium at a ow rate of 5 mL min −1 into the collision/reaction chamber.…”
Section: 23mentioning
confidence: 99%
“…282 The sample and LAMP reagents were mixed and encapsulated in agarose droplets, generated by inhouse fabricated centrifugal droplet generators, and only agarose particles, containing virus DNA were labelled with Ru compound. The copy number of virus DNA was estimated from the 101 Ru : 153 Eu ratio detected using SV-ICP-MS. The lowest quantication achieved was 25 copy per mL virus DNA in one analysis without the need for a calibration curve.…”
Section: Engineered Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Moreover, lignocellulosic-derived feedstocks are composed of phospholipids found in the plasma membrane of cells [61]. A previous study revealed that PCs are the main phospholipids in the outermost sapwood of pine, and vital for plasma membrane formation [62].…”
Section: Phospholipidsmentioning
confidence: 99%